THE ANIMATION OF ANTICIPATION SIMULATION OF FLOOD DISASTER BASED ON INFOGRAPHIC (CASE STUDY OF WATERSHED IN MEDAN JOHOR REGION, MEDAN CITY) - Junus Sinuraya; Hikmah Adwin Adam (Sean Institute, 2021)
Flood disaster is a natural phenomenon caused by the natural process and uncontrolled human activities in exploiting nature. The natural process depends on rainfall conditions, groundwater systems (geohydrology), geological structure, rock types, geomorphology, and topography. Meanwhile, human activities mean behaviors in exploiting nature for human welfare, that tend to damage the environment, particularly at a watershed, with high intensity, less control, and oversteps of the spatial planning rules. It has been known that flood disaster brings a big loss, for example, the physical loss is estimated more than a billion rupiah and it has not included tangible losses (or invaluable losses), such as plague, the time loss of social activity, and so forth. It is expected to minimize the loss by flood anticipation from government and society who are prone to getting the flood impact, for example, the settlement at the watershed. This research aims to design and make an infographic of flood anticipation simulation based on animation and multimedia for giving education to the society who are often getting the flood impact, like the settlement at the watershed, so that the physical and intangible losses can be minimized